Leishman and Giemsa stain: a new reliable staining technique for blood/bone marrow smears. (30th July 2015) - Gajendra, S.; Jha, B.; Goel, S.; Sahni, T.; Sharma, R.; Shariq, M.; Jaiswal, S.; Sachdev, R.
Summary: Introduction: Peripheral blood and bone marrow smear examination is an important basic tool for the diagnosis of different haematological conditions including haematological malignancies. We created a newer modification of the conventional Leishman and Giemsa stains as Leishman and Giemsa (L&G) stain and compared the efficacy and reliability of this stain with conventional stains. The study was performed to evaluate the staining efficacy, feasibility, time and cost of L&G stain over the conventional Leishman and Giemsa stains. Methods: A pilot study was carried out in the Department of Haematology of our hospital from October 2013 to December 2013. Hundred selected cases, each with peripheral blood and bone marrow smears were taken, and three sets of the smears were prepared from each sample – one for L&G stain and other two – one each for conventional Leishman and Giemsa stains. This staining is further incorporated in our routine standard operating protocols for staining of all the peripheral blood smears in automated stainer, Sysmex SP10. Result: The average grading score from each staining methods from all the three experts was compiled. The average grading score of L&G staining method was noted to be significantly higher than the other two methods (analysis of variance test, P value < 0.05). When modified L&G stain (C) was compared with stain conventional stains (A and B), a P value of <0.001 was noted in all parameters except between Leishman stain and L&G stain in mature RBC and WBC nucleus and RBC inclusions ( P value between 0.05 and 0.001). Conclusion: L&G staining is a newer staining technique of immense help in high‐throughput haematology laboratories by offering a time‐saving, cost‐effective and better staining option to conventional staining methods. It gives a better nuclear and cytoplasmic differential staining and can also be used in automated blood counters/stainer.